Mathematical analysis of deterministic and stochastic problems in complex media electromagnetics - Roach, G. F. (Princeton University Press, 2012)
Electromagnetic complex media are artificial materials that affect the propagation of electromagnetic waves in surprising ways not usually seen in nature. Because of their wide range of important applications, these materials have been intensely studied over the past twenty-five years, mainly from the perspectives of physics and engineering. But a body of rigorous mathematical theory has also gradually developed, and this is the first book to present that theory. Designed for researchers and advanced graduate students in applied mathematics, electrical engineering, and physics, this book introduces the electromagnetics of complex media through a systematic, state-of-the-art account of their mathematical theory.
Keywords: Electromagnetism -- Mathematics.; Stochastic control theory.; Mathematical analysis.; elektronické knihy; electronic books